Proposal of successive interference cancellation scheme in optical code-division multiple access systems - Eltaif, Tawfig; Shalaby, Hossam M. H.; Shaari, Sahbudin; Hamarsheh, Mohammad M. N. (SPIE-SOC PHOTOPTICAL INSTRUMENTATION ENGINEERS, 2008)
Proposes one of the multiuser detection schemes, a new technique that has the potential to reduce interference or suppress multiple-access interference and, therefore, increase the capacity of optical code-division multiple access (CDMA) systems. It is a successive interference cancellation (SIC) scheme known as a low-complexity multiuser detection method for direct sequence CDMA systems. A SIC scheme is analyzed using an optical orthogonal code, with a different power for each user, that takes into account the impact of imperfect interference cancellation. (C) 2008 Society of Photo-Optical Instrumentation Engineers.